Pengembangan Modul Pembelajaran Pendidikan Agama Islam (PAI) Kelas IV Madrasah Ibtidaiyah - Laila Nursafitri; Widi Widaryanto; Ahmad Zubaidi (INVENTA: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
Learning module to be one of print media learning for students. This study aims to develop learning modules for Islamic Education (PAI) grade IV Madrasah Ibtidaiyah. Development of learning modules implemented in six phases: (1) formulating the problem/research objectives, (2) conducting preliminary studies; (3) designing development; (4) implement development; (5) evaluating products, data analysis, and reflection; and (6) reporting the research result. Product validation with focus group discussion (FGD) techniques. FGD participants are a lecturer and subject-matter teachers. The trial through The One Group Pretest-Posttest Design experiment. The results showed that students' mean value increased. The mean of score 60 increased to 86.7. It can be said that this PAI learning module effectively used in learning.